Anastomotic Ulcers After Ileocolic Resection for Crohn's Disease Are Common and Predict Recurrence. Issue 7 (19th October 2019) - Hirten, Robert P; Ungaro, Ryan C; Castaneda, Daniel; Lopatin, Sarah; Sands, Bruce E; Colombel, Jean Frederic; Cohen, Benjamin L
Abstract: Background: Crohn's disease recurrence after ileocolic resection is common and graded with the Rutgeerts score. There is controversy whether anastomotic ulcers represent disease recurrence and should be included in the grading system. The aim of this study was to determine the impact of anastomotic ulcers on Crohn's disease recurrence in patients with prior ileocolic resections. Secondary aims included defining the prevalence of anastomotic ulcers, risk factors for development, and their natural history. Methods: We conducted a retrospective cohort study of patients undergoing an ileocolic resection between 2008 and 2017 at a large academic center, with a postoperative colonoscopy assessing the neoterminal ileum and ileocolic anastomosis. The primary outcome was disease recurrence defined as endoscopic recurrence (>5 ulcers in the neoterminal ileum) or need for another ileocolic resection among patients with or without an anastomotic ulcer in endoscopic remission. Results: One hundred eighty-two subjects with Crohn's disease and an ileocolic resection were included. Anastomotic ulcers were present in 95 (52.2%) subjects. No factors were associated with anastomotic ulcer development. One hundred eleven patients were in endoscopic remission on the first postoperative colonoscopy. On multivariable analysis, anastomotic ulcers were associated with disease recurrence (adjusted hazard ratio [aHR] 3.64; 95% CI, 1.21–10.95; P = 0.02). Sixty-six subjects with anastomotic ulcers underwent a second colonoscopy, with 31 patients (79.5%) having persistent ulcers independent of medication escalation. Conclusion: Anastomotic ulcers occur in over half of Crohn's disease patients after ileocolic resection. No factors are associated with their development. They are associated with Crohn's disease recurrence and are persistent. Abstract : It is controversial whether anastomotic ulcers represent Crohn's disease reoccurrence after ileocolic resection and should be included in the Rutgeerts score. We found anastomotic ulcers are common after ICR, are associated with increased risk of disease reoccurrence, and are persistent.